Ilmu-ilmu Kemanusiaan Dalam Ranah Sains dan Teknologi di Indonesia : Studi Kasus ITB - Prof. Dr. Setiawan Sabana, MFA (Fakultas Seni Rupa dan Desain ITB, 2006)
Higher education in Indonesia tends to appreciate education of science and technology more than the other field of studies. This condition seems prominent at a higher education specialising in the field of science and technology such as Institut Teknologi Bandung. However, Institut Teknologi Bandung – as one of the oldest higher education in Indonesia – has learnt the importance of the role of humanities for solving the social problems because of the fact that science and technology only cannot be used to solve the current world's social problems. In the past ten years, those involved in the group of sciences (KK) of humanities in ITB have been trying to establish a study program. This group, however, has not yet achieved this target. It is because of the fact that the field of humanities have so wide range of subjects that make this group have difficulty creating the right scientific system and using the right scientific methodology for this study program specialising in solving the social problems. Since the social problems can be viewed from both the humanities and social sciences, it is necessary that social sciences be taken into account in solving the social problems. Although the domain of humanities is slightly different from the one of social sciences, combining them is possible in relation with the KK formation for the sake of solving the social problems. Hence, the present KK of humanities can be transformed into the KK consisting of social sciences and humanities. And this transformation is relevant within the context of involving the social sciences and humanities